1997
DOI: 10.21236/ada329276
|View full text |Cite
|
Sign up to set email alerts
|

Potential Military Effects on Selected Plant Communities in the Southeastern United States

Abstract: Military training and testing mission requirements make up the highest priority land uses on Department of Defense (DoD) lands. The U.S. Armed Forces require realistic, relatively natural, and expansive areas for adequate training. Training activities can lead to degradation of sensitive natural resources, but they also produce benefits. An ecosystem-based approach to managing threatened, endangered, and sensitive species (TES) and other natural resources provides DoD with an efficient, effective, and flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Scrub communities are closely associated with xeric longleaf pine sandhills and other pyrogenic plant communities. Earlier reports from this SERDP work unit include summaries of management recommendations for a number of these associated communities (Harper et al 1997 andHohmann, 1998). While conducting research for this report, researchers found management recommendations pertaining to species inhabiting both scrub and longleaf pine woodlands that tended to be biased toward longleaf pine.…”
Section: Scopementioning
confidence: 97%
See 2 more Smart Citations
“…Scrub communities are closely associated with xeric longleaf pine sandhills and other pyrogenic plant communities. Earlier reports from this SERDP work unit include summaries of management recommendations for a number of these associated communities (Harper et al 1997 andHohmann, 1998). While conducting research for this report, researchers found management recommendations pertaining to species inhabiting both scrub and longleaf pine woodlands that tended to be biased toward longleaf pine.…”
Section: Scopementioning
confidence: 97%
“…This report is to be used by DoD natural resource policy makers, installation land managers, and the natural resource research community, in conjunction with associated documents produced under this SERDP work unit (e.g., Trame and Harper 1997; as well as Trame and Tazik 1995) to (1) develop ecosystem-based approaches to describe natural communities and TES habitat in relation to military activities, (2) evaluate military-related effects on those communities, (3) develop community-based strategies for supporting both military land use and TES habitat management, and (4) develop management solutions for military impacts to natural communities when management for TES habitat is a priority for a particular location.…”
Section: Mode Of Technology Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few human-based activities have been found to benefit some wildlife species and plant communities (e.g., prescribed burning; USFWS 1991USFWS , 2000LeBlond et al 1994;Trame and Harper 1997), most have deleterious effects (USFWS 1982(USFWS , 1983(USFWS , 1987(USFWS , 1990a(USFWS and b, 1991(USFWS , 1992(USFWS , 1994(USFWS , 1995(USFWS , 1996(USFWS , 1998(USFWS , 2000. Studies have investigated the impacts for many different types of human disturbances on wildlife, such as:…”
Section: A Literature Review Of Sound Research On Animalsmentioning
confidence: 99%
“…This report is to be used by DoD natural resource policymakers, installation land managers, and the natural resource research community, in conjunction with associated documents produced under this SERDP work unit (e.g., Trame and Harper 1997;Harper and Trame, in prep;and Trame and Tazik 1995) to (1) develop ecosystem-based approaches to describe natural communities and TES habitat in relation to military activities, (2) evaluate military-related effects on those communities, (3) develop community-based strategies for supporting both military land use and TES habitat management, and (4) develop management solutions for military impacts to natural communities when management for TES habitat is a priority for a particular location.…”
Section: Mode Of Technology Transfermentioning
confidence: 99%